Impelementasi Kegiatan Keagamaan untuk Membentuk Karakter Religius: Sebuah Strategi Pendidik - Sururun, Eni; Zamroni, M Afif; Rusydi, Ibnu (Interdisciplinary Journal of Social Sciences, 2024)
This research aims to explore the religious character values instilled in students at MI Al Hidayah Bangli, as well as the strategies applied in shaping these characters through religious activities. The study utilizes a qualitative method with data collection techniques through interviews, observations, and documentation. The research findings reveal nine religious character values developed, namely piety, courtesy, honesty, responsibility, gratitude, sincerity and humility, discipline and time appreciation, caring and respect, as well as respecting others' opinions and collaboration abilities. The applied strategies include role modeling, discipline cultivation, habituation, creating a conducive environment, as well as integration and internalization of character values in various religious activities. These strategies have a positive impact on students, such as improving noble morality, social spirit, honesty, justice, consistency, and loyalty. The research concludes that MI Al Hidayah Bangli endeavors to instill and develop religious characters in students through various strategies in religious activities that are consistently and continuously implemented and provide positive effects on students' character development, which are expected to be implemented in daily life.